Meningkatkan Kemampuan Berpikir Kreatif Menggunakan Model Pembelajaran Discovery Learning - Sari Aprilia Leksani; Erliany Syaodih; Ilyas (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2018)
The cause of the students are low student knowledge, the ability of students to be low, students 'thinking is still not creative, students' attitude in learning tends to be lazy, and the cause of the teacher is the method of learning is not appropriate. One of the learning models that can guide students into a cognitive thinker is the learning model of Discovery Learning. To handle the problem of students who are less creative then this learning model is suitable to improve student creativity. This research was conducted in SENIOR HIGH SCHOOL 11 Bandung with sample selection based on purposive sampling where sample XI SOCIAL 2 which become experimental class and XI SCIENCE 2 which become control class. The results of this study were obtained as follows: (1) There is an increase in the ability to think creatively in writing high school students after applied learning model Discovery Learning (2) Improvement of creative thinking skills in writing high school students whose learning using learning model Discovery Learning is better than students who use Scientific learning in general.